Electric vehicle charging/discharging station (EVCDS)-VI : a communication network and a central server - Paw, Su Yuan. (2011)
Conventional gas-driven vehicles (GDV) cause air pollution and global warming due to CO2 emission. Electric vehicles (EV) which can be charged by renewable energy systems such as Photovoltaic (PV) system will gradually replace GDVs in future. Singapore government has decided to set aside a sum of $20 million for the trial that will put the first Electric Vehicles (EVs) on the roads from next year. Therefore the public facilities for EV charging/discharging will be needed.